Impact of left atrial appendage thrombus location on diagnostic accuracy of cardiac CT: a single-centre case-control study - Ye Tian; Jing Tan; Haiyan Ma; Jing Huang; Zhi Jiang; Chuxian Guo; Qifang Liu; Longhai Tian; Qiaoqiao Ou; Long Yang; Jionghong He; Yuquan Wang (BMJ Open)
Objective Cardiac CT (CCT) is an emerging non-invasive modality for assessing left atrial appendage (LAA) thrombus, but the results were conflicting. Our study aims to evaluate the accuracy of CCT for detecting LAA thrombus in patients undergoing catheter ablation of atrial fibrillation, using trans-oesophageal echocardiography (TEE) as the reference standard.Design Case-control study.Setting Patient data were collected from a tertiary hospital in China between 2017 and 2022.Participants The study enrolled 726 patients (male: 60.2%, age: 61±11 years) who had both TEE and CCT before catheter ablation of atrial fibrillation.Measures The CCT protocol consisted of one angiographic phase and one delayed scan 30 s later. LAA thrombi were defined as solid masses on TEE or persistent defects on CCT. The thrombus dimension and location, the LAA filling and emptying flow velocity were assessed by TEE.Results Of the 57 (7.9%) patients with LAA thrombi identified by TEE, 29 (50.9%) were located at the LAA ostium, and 28 (49.1%) were in the LAA. The former showed higher motility following blood flow and heartbeats than the latter. The CCT detected 14 (48.3%) of the LAA-ostium thrombi but 25 (89.3%) of those in the LAA (p=0.001). The LAA-ostium thrombi with the LAA mean flow velocity >0.35 m/s and maximum diameters <10 mm were more prone to have CCT false-negative results.Conclusion For patients undergoing catheter ablation for atrial fibrillation, CCT with a 30 s delay scan is less sensitive to LAA thrombi than TEE, especially for LAA-ostium thrombi with smaller sizes and higher LAA flow velocity.